CRITIQUE OF THE CONCEPT OF GENDER FEMINIST INTERPRETATION: A REVIEW OF CONTEMPORARY INTERPRETATIONS: KRITIK KONSEP GENDER PENAFSIRAN FEMINIS: TELAAH TAFSIR-TAFSIR KONTEMPORER - Rizqi Ramadhan; Amroeni Drajat; Mardian Idris Harahap (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This thesis aims to examine and critique the concept of gender in feminist interpretations of the Qur’an through a comparative (muqarran) study of contemporary exegeses. The study’s background highlights a shift in the meaning of “gender” from a biological category of sex to a social construct that can alter perceptions of a person’s sex, and the impact of this shift on the interpretation of Qur’anic verses concerning women specifically issues of leadership (Qur’an, an-Nisaʾ 4:34), polygyny (an-Nisaʾ 4:3), and inheritance distribution (an-Nisaʾ 4:11). The author analyzes contemporary tafsirs as an effort to clarify and counteract distortions in the interpretation of these Qur’anic verses related to the concept of gender. This research uses a qualitative method with a library-based approach and comparative (muqarran) analysis to contrast different interpretations. The study maps the methods and interpretive tendencies of feminist exegetes such as Amina Wadud, Zaitunah Subhan, and Nasaruddin Umar, and compares them with contemporary tafsirs including Tafsīr al-Munīr by Wahbah az-Zuhailī, Tafsīr al-Azhar by Buya Hamka, and Tafsīr al-Misbāḥ by Quraish Shihab. The findings identify several critiques of feminist interpretations of the gender concept: (1) feminist readings consistently emphasize that women are discriminated against by men in Islamic teachings and the Qur’an—portraying Islam as perpetuating patriarchal culture—which may create the misconception that Islam is discriminatory toward women; (2) there are misconceptions about the concept of gender from an Islamic perspective, such as treating gender as a form of relativism that precludes absolute truth, and using the gender concept to justify sexual deviations (e.g., the increasing visibility of LGBT cases); and (3) several negative social impacts of feminist exegesis on Muslim communities, for example: declining marriage rates due to women’s reluctance to accept male leadership in the household, widespread rejection and moves to prohibit polygyny, and resistance to Qur’anic inheritance rules. The thesis concludes by underlining the need for critical reading of feminist gender concepts in Qur’anic interpretation and for comparing them with other contemporary tafsirs. Such balanced readings—attending both to text and context—can correct conceptual and practical deviations in the discourse on gender among Muslim communities, and prevent Islam from being perceived as discriminatory toward women. Islam, in fact, upholds the dignity and worth of every human being, both male and female, and is rahmatan lil-ʿālamīn.